Architect Jerko Marasović - Renaissance Man of the Twentieth Century (Prostor, 2024)
The book was published in collaboration between the Split Architects Society and the Faculty of Architecture in Zagreb to mark the centenary of the birth of Jerko Marasović (1923–2009), a prominent Croatian architect of the 20th century, particularly significant in the field of research, scientific study, and restoration of Diocletian's Palace and the historic core of Split. In addition to his dominant work in the research, preservation, and restoration of architectural heritage, he was also involved in photography, meteorology, design, inventing, and shipbuilding. Due to the breadth of his interests and diverse fields of activity, many recognized him as a distinguished Renaissance man.